Facilitating a Psychologically Safer Climate in Simulation-Based Education with Healthcare Learners: A Systematic Review of Effectiveness - Jackson, Ashley (Université d'Ottawa / University of Ottawa, 2022)
Simulation is considered a safe space for learning as no patient harm could occur. However, learner safety is equally significant to consider. Despite increased interest in simulation psychological safety, evidence synthesis to support the effectiveness of interventions remains lacking. This systematic review seeks to determine what interventions are effective for establishing and maintaining psychological safety within the three phases of simulation with healthcare learners. A Joanna Briggs Institute systematic review of effectiveness was conducted in accordance with the preferred reporting items for systematic reviews and meta-analyses. Articles published from 2011 to 2022 and their references from six databases were searched. Eight articles were included in the analysis. Psychological safety interventions were grouped into two categories: (1) single or (2) multidimensional. Single interventions were more likely to improve learner psychological safety. Several interventions can be used during all phases of simulation to foster a psychologically safer simulation learning environment.
Keywords: Psychological safety; Nursing student; Healthcare student; Simulation